2017
DOI: 10.1101/158766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust diagnosis of Ewing sarcoma by immunohistochemical detection of super-enhancer-driven EWSR1-ETS targets

Abstract: Ewing sarcoma is an undifferentiated bone-associated cancer. Although molecular detection of pathognomonic EWSR1-ETS fusions such as EWSR1-FLI1 enables definitive diagnosis, substantial confusion can arise if molecular diagnostics are unavailable. Diagnosis based solely on the conventional immunohistochemical marker CD99 is unreliable due to its abundant expression in morphological mimics. This study aimed to identify novel diagnostic immunohistochemical markers for Ewing sarcoma.We analyzed 768 expression mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…1a). These data were validated on the protein level in a tissue microarray 23,24 comprising the same normal tissue types and cancer entities (Fig. 1b,c).…”
Section: Sox6 Is Highly But Variably Expressed In Ewsmentioning
confidence: 81%
See 2 more Smart Citations
“…1a). These data were validated on the protein level in a tissue microarray 23,24 comprising the same normal tissue types and cancer entities (Fig. 1b,c).…”
Section: Sox6 Is Highly But Variably Expressed In Ewsmentioning
confidence: 81%
“…To explore the expression pattern of SOX6, we took advantage of a well-curated set of >750 DNA microarrays, which we established previously 23,24 , comprising 18 representative normal tissues types and 10 cancer entities. Comparative analyses revealed that SOX6 is overexpressed in EwS relative to normal tissues and other cancers (Fig.…”
Section: Sox6 Is Highly But Variably Expressed In Ewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent large series (assessing a combined 70 cases) both reported a sensitivity of 93% 105,106. However, assessments across the spectrum of round cell tumors have shown this marker is not entirely specific 105,107. Consequently, it is currently best utilized as part of a wider panel; immunohistochemistry has not supplanted the use of molecular confirmation in difficult/atypical cases.…”
mentioning
confidence: 99%
“…In addition, strong and diffuse nuclear staining for WT1 and ETV4 aids in their distinction from Ewing sarcoma or BCOR-rearranged round cell sarcoma [9]. A similar situation could be seen in BCOR [10], or even in NFATc2-rearranged sarcoma [11].…”
Section: What Makes a Group Of Tumors Become A Clinical Entity? A Simmentioning
confidence: 94%